2010
DOI: 10.1016/j.physletb.2010.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Event-by-event jet quenching

Abstract: High momentum jets and hadrons can be used as probes for the quark gluon plasma (QGP) formed in nuclear collisions at high energies. We investigate the influence of fluctuations in the fireball on jet quenching observables by comparing propagation of light quarks and gluons through averaged, smooth QGP fireballs with event-by-event jet quenching using realistic inhomogeneous fireballs. We find that the transverse momentum and impact parameter dependence of the nuclear modification factor R AA can be fit well i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
4

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 35 publications
3
35
4
Order By: Relevance
“…The smaller R AA in the case of fluctuating initial conditions obtained in the present study is opposite to the results reported in previous studies based on a static medium [24] or 2+1 dimensional ideal hydrodynamics [25], where a larger R AA was obtained when initial fluctuations were included. To understand this difference, we define the jet energy loss difference δ ∆E ≡ ∆E fluc − ∆E smth between the average energy loss calculated with fluctuating initial conditions and that with smooth initial conditions.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The smaller R AA in the case of fluctuating initial conditions obtained in the present study is opposite to the results reported in previous studies based on a static medium [24] or 2+1 dimensional ideal hydrodynamics [25], where a larger R AA was obtained when initial fluctuations were included. To understand this difference, we define the jet energy loss difference δ ∆E ≡ ∆E fluc − ∆E smth between the average energy loss calculated with fluctuating initial conditions and that with smooth initial conditions.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results are opposite to those found in Ref. [24] for a static medium and also those in Ref. [25] using a 2+1 ideal hydrodynamics and with the jet energy loss depending on the local energy density, which show a reduced jet energy loss in the QGP for the fluctuating initial conditions.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…First we have calculated the prompt photon (direct + fragmentation) spectra and the fast quark spectra at LO of strong coupling (α s ) with the code JETPHOX (Aurenche et al, 2006). Next we have used the fireball model PPM (Rodriguez et al, 2010) to evaluate the back-scattering photon yield while accounting for (i) the energy loss of partons and (ii) the energy loss trigger of jets.…”
Section: Resultsmentioning
confidence: 99%